Evaluasi Kinerja Instalasi Farmasi Di Rsud Dr.Soehadi Prijonegoro Sragen Atas Pelayanan Pasien Rawat Jalan Periode Mei-Juli 2016 - Dekaningtyas, Hevi, Drs. Suharsono, Apt., Sp.FRS, Gunawan Setiyadi, M.Sc., Apt (2016)
Mininum Service Standards (MSS) for Hospital is provision of type and quality of basic service that must become a district business earned every citizen is entitled to a minimum and specification technic for minimum benchmark of service provided by the Public Service Board to the society. One of the 21 minimum service standards (MSS) hospital is a Pharmaceutical Services MSS.The purpose of this study was to survey the performance of the pharmacy installation in RSUD dr. Soehadi Prijonegoro Sragen and outpatient service in term of performance indicators customer satisfaction, waiting time drug supply, and waiting time personalized drug 2016.This study was an observational research (non-experimental) by using descriptive method. The instrument that used in this study was a questioner and data collectors sheet, the research subjects was the patient or the family of the patient as many as 150 respondents. The satisfaction level of patients include reliability, responsiveness, drug information services, the attitude of the officers, and the tangible facilities. As for the waiting time starting from the screening prescriptions to patients receiving the drug. The result showed the level of outpatient satisfaction at 60% does not meet the MSS for Hospital and the average time of waiting time drug supplyfor the outpatient at 46,3 minutes does not meet the MSS for Hospital, the average time of waiting time personalized drugat 71,3 minutesdoes not meet the MSS for Hospital.